Delay in the diagnosis and treatment of breast cancer in Vietnam. (19th October 2021) - Nguyen, Sang M.; Nguyen, Quang T.; Nguyen, Lan M.; Pham, Anh T.; Luu, Hung N.; Tran, Huong T. T.; Tran, Thuan V.; Shu, Xiao‐Ou
Abstract: Background: Delays in diagnosis and treatment from first noticeable breast cancer symptoms are associated with poor outcomes. Understanding the reasons and barriers for patients' delay in seeking medical care is critical to mitigating the problem. Methods: In‐person surveys were conducted among 462 women, aged 18–79, with incident breast cancer cases, recruited from two cancer hospitals in North Vietnam. Delay, defined as the time interval between symptom recognition to the diagnosis and initiation of treatment equal to or exceeding 3 months, was categorized as follows: no delay (<3 months), moderate delay (3–8 months), and serious delay (≥9 months). Multivariable multinomial logistic regression was applied in data analyses. Results: Over one‐quarter patients (31.5%) experienced moderate delays, and close to one‐fifth (17.5%) experienced serious delays. Adjusted odds ratios and 95% confidence intervals for moderate and serious delays were 5.60 (3.00–10.47) and 4.25 (2.05–8.85) for financial and physical barriers, respectively. Moderate delay was positively associated with psychological barriers (5.55 [1.75–17.57]) and lack of proper knowledge (3.15 [1.47–6.74]). The associations of barriers with delays in diagnosis and treatment appeared stronger among women living in rural areas. A lack of proper knowledge was significantly associated with delay among young women (<45 years old) and those with high incomes, while psychological barriers were significantly associated with delay among older women (≥45 years old). Conclusion: Delays in diagnosis and treatment are common among Vietnamese breast cancer patients and are affected by several noted barriers. Proper policy needs to be developed to address this public health issue. Abstract : A case cohort study found that delay in diagnosis and treatment of breast cancer is common among Vietnamese women and is affected by financial and physical barriers, psychological barriers, and lack of proper knowledge. Proper policy needs to be developed accordingly to address this public health issue.